Cynandione A Alleviates Neuropathic Pain Through α7-nAChR-Dependent IL-10/β-Endorphin Signaling Complexes - Han, Qiao-Qiao; Yin, Min; Wang, Zi-Ying; Liu, Hao; Ao, Jun-Ping; Wang, Yong-Xiang (Frontiers in Pharmacology, 2021)
Cynandione A, an acetophenone isolated from Cynanchum Wilfordii Radix, exhibits antineuropathic pain effect. This study further explored the target molecule and signaling mechanisms underlying cynandione-A-induced antineuropathic pain. Intrathecal injection of cynandione A significantly attenuated mechanical allodynia in neuropathic rats and substantially increased spinal expression of IL-10 and β-endorphin but not dynorphin A. Cynandione A treatment also enhanced expression of IL-10 and β-endorphin but not α7 nicotinic acetylcholine receptors (nAChRs) in cultured microglia. The IL-10 antibody attenuated cynandione-A-induced spinal or microglial gene expression of β-endorphin and mechanical allodynia, whereas the β-endorphin antiserum blocked cynandione-A-induced mechanical antiallodynia but not spinal or microglial IL-10 gene expression. The α7 nAChR antagonist methyllycaconitine significantly reduced cynandione-A-induced mechanical antiallodynia and spinal or microglial expression of IL-10 and β-endorphin. Furthermore, cynandione A stimulated microglial phosphorylation of PKA, p38, and CREB in an α7-nAChR-dependent manner, and treatment with their inhibitors attenuated cynandione-A-induced mechanical antiallodynia and spinal or microglial expression of IL-10 and β-endorphin. In addition, cynandione A stimulated spinal phosphorylation of the transcription factor STAT3, which was inhibited by methyllycaconitine, the PKA activation inhibitor or IL-10 antibody. The STAT3 inhibitor NSC74859 also abolished cynandione-A-induced mechanical antiallodynia and spinal expression of β-endorphin. These findings suggest that cynandione A suppresses neuropathic pain through α7-nAChR-dependent IL-10/β-endorphin signaling pathway in spinal microglia.